HUBUNGAN HASIL BELAJAR MATA PELAJARAN PRODUKTIF DENGAN MINAT MEMBUKA USAHA BUSANA - Dwi Yuliasih (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2016)
The research aimed to analyze therelation of learning result of productivesubjects with interest to open fashionbusiness at Vocational State Senior HighSchool (SMKN) 6 Yogyakarta. Thisresearch is a type of ex-post factoresearch with data collection methodsusing questionnaires and documentation.Data analysis techniques usingdescriptive analysis techniques andhypothesis test using Product Momentcorrelation test preceded testrequirements analysis, the test ofnormality and linearity. The resultsshowed there was a positive andsignificant relationship between thelearning result of productive subjectswith the interest of opening a fashionbusiness, with a contribution of 20.7%.Productive subjects can equip SMKstudents to produce the new innovationsthat are needed when they open abusiness